Recent and Rapid Radiation of the Highly Endangered Harlequin Frogs (Atelopus) into Central America Inferred from Mitochondrial DNA Sequences - Juan P. Ramírez; César A. Jaramillo; Erik D. Lindquist; Andrew J. Crawford; Roberto Ibáñez (Diversity, 2020)
Populations of amphibians are experiencing severe declines worldwide. One group with the most catastrophic declines is the Neotropical genus Atelopus (Anura: Bufonidae). Many species of Atelopus have not been seen for decades and all eight Central American species are considered “Critically Endangered”, three of them very likely extinct. Nonetheless, the taxonomy, phylogeny, and biogeographic history of Central American Atelopus are still poorly known. In this study, the phylogenetic relationships among seven of the eight described species in Central America were inferred based on mitochondrial DNA sequences from 103 individuals, including decades-old museum samples and two likely extinct species, plus ten South American species. Among Central American samples, we discovered two candidate species that should be incorporated into conservation programs. Phylogenetic inference revealed a ladderized topology, placing species geographically furthest from South America more nested in the tree. Model-based ancestral area estimation supported either one or two colonization events from South America. Relaxed-clock analysis of divergence times indicated that Atelopus colonized Central America prior to 4 million years ago (Ma), supporting a slightly older than traditional date for the closure of the Isthmus. This study highlights the invaluable role of museum collections in documenting past biodiversity, and these results could guide future conservation efforts. An abstract in Spanish (Resumen) is available as supplementary material.